Development of Lecturer Data Management System Using Asynchronous JavaScript & XML (AJAX) Concepts - I Komang Budi Mas Aryawan (Jurnal Informatika, 2022)
Good data management can help leaders or policymakers in determining a decision. This research aims to properly manage lecturer data at the Faculty of Agricultural Technology, Udayana University. This study uses the waterfall software engineering development method with the following stages: (1) Analysis, conducting analysis related to software requirements, such as how the system works, menu features used, and so on. (2) Design, perform database design, and design the system interface. (3) Coding, implementing the design into a software program. This system was developed using SQL queries on the database, PHP and JavaScript programming languages, HTML markup languages, and bootstrap framework. The concept of Asynchronous JavaScript and XML (AJAX) is applied when compiling program code. (4) Testing, conducting tests on a series of programs to ensure the system's functionality can function properly by using the black box testing method. The results showed that 94% of respondents stated that the system could make it easier to manage lecturer data and the results of system testing showed that the system functionality was running well according to the test scenario.